SYNTHESIS BETWEEN DIGITAL MARKETING STRATEGIES AND CHESS STRATEGIES (Heritage, 2020)
Chess players understand that good strategic decisions require taking into account the probable moves and counter moves of opposing players. They study the approach of their opponents and identify the probable sequence of moves that will follow. Looking both forward and backward, they adjust their moves and their strategy that leads them to victory in this game. There are many practical examples in which organizations have used chess strategies, which have been developed for hundreds of years, to outsmart their competitors in the market. It is possible to draw a parallel between the strategies of this ancient social game and the business environment, and the knowledge and experience of professional chess players can also help marketing professionals gain a competitive advantage in the market and achieve their business goals in the digital environment. Being willing to make sacrifices for the sake of long-term gain, creativity and experimentation, but also adaptability and readiness for continuous learning, are just some of the similarities that characterize these two areas. For this reason, the main goal of this paper is to draw the attention of professionals in the field of digital marketing, to all the possible benefits of implementing chess strategies in business strategies. The subject of the research is to identify and examine the efficiency and effectiveness of chess strategies, which when adapted to the real business environment can have a positive impact on consumer behavior, but also help companies predict the strategies of direct and indirect competitors in the market, and to respond to them in a timely and adequate manner.
Keywords: Chess, Chess Strategies, Digital Marketing, Digital Marketing Strategies, Consumer Behavior, Competition